2021
DOI: 10.1016/j.jesf.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social distancing during the COVID-19 pandemic on physical activity in children: A scoping review of the literature

Abstract: Background/objectives There is an urgent concern about physical inactivity among children caused by recent restrictions for containing the spread of the novel coronavirus disease (COVID-19). This scoping review aims to identify the impact of the pandemic and related factors on children's physical activity (PA). Methods Twenty-one studies published in 2020 that evaluated PA among children under the age of 18 were extracted from electronic databases. The survey contexts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 60 publications
(73 reference statements)
7
82
1
6
Order By: Relevance
“…Women, especially those going through menopause, can increase their physical activity levels by making plans, setting goals, and exercising with friends or family (Lum and Simpson, 2021 ). Moreover, parental support may help children maintain or increase their physical activity levels during a pandemic (Yomoda and Kurita, 2021 ).…”
Section: An Integrated Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Women, especially those going through menopause, can increase their physical activity levels by making plans, setting goals, and exercising with friends or family (Lum and Simpson, 2021 ). Moreover, parental support may help children maintain or increase their physical activity levels during a pandemic (Yomoda and Kurita, 2021 ).…”
Section: An Integrated Conceptual Frameworkmentioning
confidence: 99%
“…Initial evidence has shown that individuals can maintain and promote mental health through exercise during the pandemic (Gupta et al, 2021 ). However, measures restricting the spread of COVID-19 have led to a decline in physical activity for most children and adolescents, especially among boys and older children and adolescents (Yomoda and Kurita, 2021 ). Compared with the first wave of the COVID-19 pandemic, physical activities in the second wave dropped by 3.1 percentage points (Gupta et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 also has had a huge impact on the quality of youth leisure time [25]. Several studies mention the considerable increase in the use of screens (television, video games, and social media) and a reduction in their physical activity [26,27]. Prolonged confinement increased the sedentary habits of the general population, carrying a risk of worsening physical health [28].…”
Section: Discussionmentioning
confidence: 99%
“…Most places where many people can gather (e.g., schools, universities, sports facilities) were closed [22]. Therefore, as movement opportunities decreased, studies consistently reported a decrease in PALs among adolescents globally [23][24][25], including in Southeastern Europe [26,27]. Not surprisingly, studies investigating PAL and changes in PAL during the COVID-19 pandemic have also aimed to determine the factors that influence PA, through comparison to investigations undertaken in "regular" circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…This was related to the higher access to sports facilities among urban adolescents in normal circumstances, and the closure of those facilities during the pandemic. Conflict with parents was negatively associated with PA, as parents who were in conflict with their children were not able to efficiently encourage their children to be physically active during the pandemic [24,28]. Moreover, a recent study evidenced that pre-pandemic sports participation and fitness status was positively associated with PALs during the pandemic, which was explained by the better physical literacy of children involved in sports, and their motivation to stay physically active even in "irregular" circumstances, such as COVID-19-imposed lockdowns [28].…”
Section: Introductionmentioning
confidence: 99%